Тайны Мадридского двора: ист.-прикл. роман : пер. с нем. (Г. Борн) - Борн Георг (1994)
Экземпляры: Ф. 10 (20020606) / Инвентарный номер: 49223 / Цена: 15.00 / Сис.шифр: 84(4/8) / Авт.знак: Б 82 / ББК: 84(4Гем)